Linking Future Tropical Precipitation Changes to Zonally‐Asymmetric Large‐Scale Meridional Circulation - Dana Raiter; Eli Galanti; Rei Chemke; Yohai Kaspi (Geophysical Research Letters)
Abstract Projected tropical precipitation changes by the end of the century include increased net precipitation over the Pacific Ocean and drying over the Indian Ocean, prompting ongoing debate about the underlying mechanisms. Previous studies argued for the importance of the zonal circulation in the longitudinally dependent tropical precipitation response, as the meridional circulation is often defined and analyzed as the zonal mean. Here we show that the projected changes in the meridional circulation are highly longitudinally dependent, and explain the zonally dependent changes in net precipitation. Our analysis exposes a zonal shift in the ascending branch of the meridional circulation, associated with a strengthened net precipitation over the central Pacific and weakened precipitation in the Indo Pacific. The zonal circulation has minor influence on these projected tropical precipitation changes. These results point to the importance of monitoring the longitudinal changes in the meridional circulation for improving our preparedness for climate change impacts.